Islamic Accounting Concept In Al-Quran And Its Implementation In Indonesia - Nurlaila Nurlaila (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
When all ‘sharia’ entities conduct Islamic financial statement presentation, the ‘sharia’ entity must be guided by PSAK 101. Allah has ordered in the surah al-Baqarah verse 282 to recording and accounting (accounting process) and so the importance of the witness as proof of transaction. Therefore, PSAK 101 should be guided to al-Baqarah verse 282. However, no one any statement which states that PSAK 101 based on al-Baqarah verse 282. There are three principles that a parameter in the Islamic accounting concept, namely accountability, justice, and truth. This research uses qualitative research. The object of this research is the concept of Islamic accounting in al-Baqarah verse 282 and PSAK 101, using primary data sources. Data collection method used is documentations and archives study of the PSAK 101 Exposure Draft Revised of 2014, the commentary of al-Quran, books, and so on. The data analysis technique used in this research is content analysis and a Likert scale to give value to the results of the data analysis. The result showed that although not found explicitly, but implicitly the concept of Islamic accounting according to al-Baqarah verse 282 has been applied in PSAk 101. This is evident from the calculation of the percentage of the third principle of the parameters in the concept of Islamic accounting in terms of PSAK objectives, scope, objectives of financial statements, the responsibility for Financial Statements, the components of Financial Statements, as well as the structure and content of PSAK 101. The result of the application are the accountability of 54.54% considered sufficient, the truth of 27.27% categorized as less-sufficient, and the justice of 18:19% considered insufficient.